Histopathology of Fusarium wilt of staghorn sumac (Rhus typhina) caused by Fusarium oxysporum f. sp. callistephi race 3. I. Modes of tissue colonization and pathogen peculiarities - Ouellette, Guillemond; Cherif, Mohamed; Simard, Marie; Bernier, Louis (Phytoprotection, 2005)
AbstractLight and transmission electron microscope studies of naturally infected or inoculated staghorn sumac plants by Fusarium oxysporum f. sp. callistephi race 3 are reported. Diverse extrinsic material (including latex in some instances) or elements occurred in vessel lumina. Some of this material labelled for pectin, often in association with tyloses, as did other opaque matter in paratracheal cells, related to alterations of their protective layer. Pronounced alterations of pit membranes of bordered pits occurred, with their outer portions disrupted into bodies of opaque matter, strongly labelled for cellulose, and their middle portions as unlabelled shreds. Similarly labelled opaque bodies occasionally occurred on vessel walls and lumina. Direct penetration of host cell secondary walls by the pathogen occurred, but these were degraded to any extent only following intramural invasion. Vessel walls, at all stages of infection, were lined with variously structured matter: in their thinnest forms, by single or paired, equidistant or widely spaced opaque bands, and in their thickest forms as alternating opaque and less opaque layers. Other thin elements, often enclosing opaque material, vesicular structures, or occasionally particles of ribosomal appearance were also delineated by similar but frequently infolded bands. These elements were sometimes observed to be confluent with fungal cells and to label for chitin. Many fungal elements were bound by only a thin or defective lucent wall layer, practically unlabelled for chitin, or by a locally thickened, labelled one; labelling for this substrate was also frequently associated with the fungal cell outer opaque wall layer or with some outer extracellular matter. Fine filamentous structures, connected to fungal cells, to the vessel lining matter, and to these other elements, extended into host walls. The lining itself generally did not label for cellulose or chitin. These observations are discussed in comparison with similar observations made regarding other wilt diseases that we have studied.